Odpowiedź :
Odpowiedź:
a)8x-2y+2x-8+20=10x-2y+12
b)2x-3+5x-5-2x+9=5x+1
c)12a+30b-12
d)5x-15y+20
e)8a+4b-9a-18b+3+3a=2a-14b+3
Szczegółowe wyjaśnienie:
a) (8x – 2y) + (2x - 8) + 20 = 8x - 2y + 2x - 8 + 20 = 10x - 2y + 12
b) (2x - 3) + (5x - 5) - (2x - 9) = 2x - 3 + 5x - 5 - 2x + 9 = 5x + 1
c) 6(2a+5b-2) = 12a + 30b - 12
d) -5(-x+3y-4) = 5x - 15y + 20
e) 4(2a + b) – 3(3a + 6b – 1 ) + 3a = 8a + 4b - 9a - 18b + 3 + 3a = 2a - 14b + 3
f) 2(7x + 2y) - 4(3x - 8y) + 3(2x - 4 ) = 14x + 4y - 12x + 32y + 6x - 12 = 8x + 36y - 12
Mam nadzieję że pomogłam i liczę na naj. ♥